Modelo de gestión administrativa para la Compañía de Transporte Mixto Pucayacu del cantón La Maná, provincia de Cotopaxi. - Esquivel Armas, Jessica Maribel (2019)
Currently, an efficient management of administrative processes is a key factor for the success of companies essentially in the field of transportation, which is why the present investigation had as its general objective the design of an administrative management model for the Company. Pucayacu Mixed Transport of La Maná county, Cotopaxi province through a situational diagnosis that allows to improve the quality of service to the users, because the organization faces multiple problems one of them is the lack of an administrative management model, this prevents that operates with an organized structure to develop an efficient administration, causing disagreement of the partners. For the fulfillment of this purpose, the use of bibliographic research was used for the collection of theoretical information, field research during the development of interviews and surveys. Among the methods used are the deductive and analytical methods that were very useful for the deduction and analysis of the results obtained through the techniques of the interview addressed to the president and the surveys made to the members and users. The situational diagnosis at the administrative level showed that there is no strategic direction and there is a lack of training in the administrative area due to the lack of an administrative management model, therefore the design of the administrative management model Malcolm Baldrige was considered pertinent. strategy on leadership, evaluation test for the administrative area, the design of a strategic direction, strategies for measuring the level of satisfaction to users through the implementation of mailboxes, the development of training on topics such as teamwork and attention to the client, which will improve each one of the administrative processes of the transport company Mixto Pucayacu.